(untitled) (Journal of the College of Basic Education, 2023)
in this research studied the structure and electrical properties of the Pure CdTe and metal Sb-doped CdTe thin films with 0.5, 1, and 1.5 wt.%, respectively. Theydeposited on glass substrates using flash evaporation technique. It was found that theprepared films had a cubic structure and a strong preferred <111> crystal orientation.Atomic force microscopy (AFM) results showed that the film surface doped Sb wasmore compact and uniform and also the root mean squared (RMS) roughnessincreased with Sb contents. The electrical properties were investigated as function ofSb wt.% doping. The results showed that the electrical conductivity (6) increasingtrend with increasing the wt.% of dopant , while the activation energies (E,i, E,2)showed an opposite trend, where the activation energies decreased with dopant.1. Introduction Thin films of II-VI semiconductors are widely used in many semiconductordevices such as photo electrochemical cells, field effect transistors, IR detectors,photodiodes, photo conductors and photovoltaic solar cells[1, 2]. CdTe has long beenidentified as a candidate for the absorber layer in low cost thin film photovoltaic solarcells because of its direct bandgap, high absorption coefficient and the possibility of avariety of preparation techniques such as close spaced sublimation (CSS)[3], vacuumdeposition [4], electrodeposition [5], and RF sputtering[6], close spaced vaportransport [7]. In this present work we focused attention on the prominent techniquesfor the deposition of thin films of multicomponent alloys whose constituents havedifferent vapor pressures. Thin films of CdTe have been prepared under suitablegrowth conditions by a simple flash evaporation (FE) technique. This techniquerequires only one boat maintained at sufficiently high temperature to evaporate theleast volatile component of the alloy. The main advantage of (FE) is that it does notrequire maintaining the critical vapor pressures of the components and temperatures ofthe boats unlike multisource thermal evaporation[8] . CdTe thin film still has many defects, such as it has extremely high resistivity. Tosolve this issue, the implying of the technique Sb-doped CdTe film to change electricalproperties [9]. In this work deposited Sb-doped CdTe films using the mixed powder of TO -AA suet Talal = - VN - Kya lal ayy cll 212 alae